Cross-talk between Helicobacter pylori and gastric cancer: a scientometric analysis - Yang, Shanshan; Hao, Shaodong; Ye, Hui; Zhang, Xuezhi (Frontiers in Cellular and Infection Microbiology, 2024)
Background Helicobacter pylori (HP) is considered a leading risk factor for gastric cancer (GC). The aim of this article is to conduct bibliometric and visual analysis to assess scientific output, identify highly cited papers, summarize current knowledge, and explore recent hotspots and trends in HP/GC research. Methods A bibliographic search was conducted on October 24, 2023, to retrieve relevant studies on HP/GC research between 2003 and 2022. The search terms were attached to HP and GC. The main data were from the Web of Science Core Collection (WoSCC). Data visualization was performed using Biblioshiny, VOSviewer, and Microsoft Excel. Results In HP/GC research, 1970 papers were retrieved. The total number of papers (Np) in HP/GC was growing from 2003 to 2022. China and Japan were in the leading position and made the most contributions to HP/GC. Vanderbilt University and the US Department of Veterans Affairs had the highest Np. The most productive authors were Peek Jr Richard M. and Piazuelo M Blanca. Helicobacter received the most Np, while Gastroenterology had the most total citations (TC). High-cited publications and keyword clustering were used to identify the current status and trends in HP/GC research, while historical citation analysis provided insight into the evolution of HP/GC research. The hot topics included the effect of HP on gastric tumorigenesis and progression, the pathogenesis of HP-induced GC (HP factors), and the mechanisms by which HP affects GC (host factors). Research in the coming years could focus on topics such as autophagy, gut microbiota, immunotherapy, exosomes, epithelial-mesenchymal transition (EMT), and gamma-glutamyl transpeptidase (GGT). Conclusion This study evaluated the global scientific output in HP/GC research and its quantitative characteristics, identified the essential works, and collected information on the current status, main focuses and emerging trends in HP/GC research to provide academics with guidance for future paths.